2018
DOI: 10.3892/mmr.2018.8685
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal estrogen gel and oral aspirin combination therapy improves fertility prognosis via the promotion of endometrial receptivity in moderate to severe intrauterine adhesion

Abstract: Intrauterine adhesion (IUA) is one of the most common gynecological diseases in women of reproductive age. IUA, particularlyin moderate to severe forms, accounts for a large percentage of infertility cases. Clinically, the first-line treatment strategy for IUA is transcervical resection of adhesion (TCRA), followed by adjuvant postoperative treatment. Estrogen is one of the classic chemotherapies used following TCRA and contributes to preventing re-adhesion following surgery. However, estrogen has limited effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 36 publications
(51 reference statements)
0
47
0
1
Order By: Relevance
“…It is worth noting that combination therapy with oestrogen and aspirin may improve the rate of pregnancy in patients with IUA (28). However, an additional study indicated that there was no significant improvement in the pregnancy rate and live birth rate following additional low dose aspirin (23).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…It is worth noting that combination therapy with oestrogen and aspirin may improve the rate of pregnancy in patients with IUA (28). However, an additional study indicated that there was no significant improvement in the pregnancy rate and live birth rate following additional low dose aspirin (23).…”
Section: Discussionmentioning
confidence: 98%
“…At present, there is increasing evidence that aspirin has a preventative effect in colorectal cancer and other types of cancer (35). Recent studies have suggested that aspirin is more effective in preventing adhesion recurrence following TcRA surgery, as it can increase endometrial angiogenesis (28). A prospective study revealed that aspirin combined with an intrauterine balloon and intrauterine device significantly increased endometrial thickness following TcRA surgery, and AFS scores and menstrual scores also improved significantly (23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of low‐dose aspirin to reduce the risk of thrombosis caused by estrogen has also been gaining attention; furthermore, aspirin facilitates blood supply to the uterine artery and spiral artery, promoting endometrial growth . Further studies have reported that postoperative application of aspirin might enhance endometrial receptivity and improve reproductive outcomes in IUA cases …”
Section: Discussionmentioning
confidence: 99%